RZYMSKIE UREGULOWANIA DOTYCZĄCE ‘INIURIA’ A KARNOPRAWNA OCHRONA CZCI W PRAWIE POLSKIM - Nowicka, Dobromiła (Zeszyty Prawnicze, 2016)
ROMAN REGULATIONS CONCERNING ‘INIURIA’ AND PROTECTION OF HONOUR AND REPUTATION IN POLISH CRIMINAL LAW Summary The aim of this article is to compare and contrast Roman and Polish criminal regulations concerning protection of an individual’s honour and reputation in two different areas: objects of legal protection, and forms of conduct liable to prosecution and providing grounds for legal action. Considerable differences may be observed between these two legal systems on both counts. While in Roman law any and every defamatory act, regardless of its form, gave rise to iniuria, Polish penal law divides non-physical acts against honour and reputation into two separate categories: pomówienie (defamation and/or slander), and zniewaga (insult). This distinction is based on the criterion of the object of legal protection: pomówienie is an attack on an individual’s reputation, while zniewaga is an attack on his dignity. The types of punishable conduct are different as well; as regards pomówienie only verbalised attacks are liable to prosecution as offences against reputation. Analysis of this matter leads to the conclusion that the distinction made in Polish criminal law for offences against honour and reputation into two different categories in consequence of the recognition of two separate objects of protection against non-physical attacks may not be the best solution.